THE MARKET CONCEPT OF THE XXI CENTURY: A NEW APPROACH TO CONSUMER SEGMENTATION - M. I. Sokolova (Vestnik MGIMO-Universiteta)
World economic development in the 21st century keeps tendencies and contradictions of the previous century. Economic growth in a number of the countries and, as a result, growth of consumption adjoins to an aggravation of global problems of the present. It not only ecology and climatic changes that undoubtedly worth the attention of world community, but also the aggravation of social problems. Among the last the question of poverty takes the central place. Poverty is a universal problem, in solution of which take part local authorities, the international organizations, commercial and noncommercial structures. It is intolerable to ignore a catastrophic situation in fight against this problem. It is necessary to look for ways of resolving it not only by using the existing methods, but also developing new approaches. One of the most significant tendencies in the sphere of fight against poverty is the development of the commercial enterprises working in the population segment with a low income level which by means of the activity help millions of people worldwide to get out of poverty. In other words, attraction of the commercial capital by an economic justification of profitability and prospects of investments into the companies working in the population segment with a low income level can be one of the methods allowing to solve effectively a poverty problem. This approach includes this population in economic activity, makes them by full-fledged participants of the market, which benefits to the creation of potential for economic growth and is a key step to getting out of poverty.